1995
DOI: 10.3109/02841869509093648
|View full text |Cite
|
Sign up to set email alerts
|

DNA Damage in Human Endothelial Cells after Irradiation in Anoxia

Abstract: Endothelial cells and fibroblasts have been reported to respond differently to oxidative stress. Both the effects of high oxygen tension and radiation involve the action of free radicals. DNA damage (single strand breaks, SSB, and double strand breaks, DSB) was assayed in human umbilical cord vein (HUV) cells and in Chinese hamster fibroblasts (V79) after irradiation under oxic or anoxic conditions. The cells were exposed to single doses in the range of 2-18 Gy of gamma-radiation from 60Co. Significantly more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Under acute hypoxia or anoxia, fewer breaks are generated due to the decreased oxygen which is normally required for the fixation of DNA damage under oxic conditions [35][36][37][38][39][40][41][42]. This is quantified by an oxygen enhancement ratio (OER), defined as the ratio of doses required for the same biological effect (e.g.…”
Section: Hypoxia Cellular Radiosensitivity and The Oxygen Enhancemenmentioning
confidence: 99%
“…Under acute hypoxia or anoxia, fewer breaks are generated due to the decreased oxygen which is normally required for the fixation of DNA damage under oxic conditions [35][36][37][38][39][40][41][42]. This is quantified by an oxygen enhancement ratio (OER), defined as the ratio of doses required for the same biological effect (e.g.…”
Section: Hypoxia Cellular Radiosensitivity and The Oxygen Enhancemenmentioning
confidence: 99%
“…In order to investigate the mechanisms for irradiation of choroidal vessels, it might also be important to evaluate the radiosensitivity of human retinal pigment epithelial cell cultures. Interestingly, Rosander and Zackrisson [17] were able to show that hypoxia increased the radioresistance of vascular endothelial cells, resulting in less DNA damage. This could be especially relevant for the treatment of hypoxia-mediated vascular proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…To compare clinical results more effectively, we used a photon beam applied by a linear accelerator, a system which is employed in clinical routine irradiation. Apart from different irradiation modi, different experimental set-ups and treatment regimens have to be compared [16][17][18], both in in vivo as well as in vitro experiments. Johnson et al [14], for example, showed a progressive cell loss in endothelial cell monolayers after irradiation with 10 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Replicating human endothelial cells in culture have shown to be affected by radiation doses as low as 6 Gray (Gy), with complete inhibition of growth at 8.7 Gy [31]. After this low-dose radiation, vascular endothelium demonstrates morphologic [32] and DNA [33,34] changes, inhibition of replication [35], and apoptosis [28]. Fibroblast proliferation and subsequent scar formation, both integral parts of AMD disease activity and progression, are also inhibited [16,36].…”
Section: Role Of Radiation In Choroidal Neovascularizationmentioning
confidence: 98%